(untitled) (Altre Modernità, 2016)
Conceived in the late thirties as “bold humanist response to Depression-era fears of runaway scientific advance and soulless industrialism” (Morrison 2012, 6), the superhero has flourished as one of the most resilient archetypes of American popular culture. This essay analyses the literary and cultural contaminations that have engendered an unprecedented revision of the paradigm since the 1980s. In particular, it will take into account three graphic novels by American cartoonist Frank Miller (1957 - ), one of leading figures of the mainstream comics renaissance, whose ideas have indelibly influenced the artistic development of both medium and genre. The Dark Knight Returns (1986), The Dark Knight Strikes Again (2002) and Holy Terror (2011) constitute an ideal Batman trilogy that charts the character’s evolution as political counterpoint to the perceived crisis of American identity. In this regard, Reaganism and 9/11 are polarized as historical discontinuities triggering the need for a new kind of a criminal (super)hero. It will be in fact demonstrated how the novels hybridise the latent generic links to hardboiled pulp novels (R. Chandler, D. Hammet) with narrative and aesthetics elements appropriated from the culturally-received concepts of terrorism and terrorists. This fruitful contamination on the one hand “play[s] with reader assumptions about genre” (Baetens and Frey 2015, 46), while on the other hand deconstructs the ideological underpinnings of the archetype, as the moral dichotomy and the alienation of justice from the law.